2014
DOI: 10.1149/2.0151411jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrode-Electrolyte Interface for Solid State Li-Ion Batteries: Point Defects and Mechanical Strain

Abstract: In this work, we present an ab-initio investigation of point defects in solid electrolyte γ-Li 3 PO 4 and in negative electrode-electrolyte interface (Li/γ-Li 3 PO 4 ). Our results on Li defects on γ-Li 3 PO 4 exhibit that Li interstitial defects dominate over vacancy defects, and that Li vacancy-interstitial pair defect formation energy in the interface is comparable to the sum of Li vacancy defect in the electrode and Li ion interstitial defects in the electrolyte region. Our study reveals that the high Li i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 57 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…This formation energy of mobile carriers may be significant for pristine, non-doped materials with highly ordered Li sublattices, and should be carefully evaluated and considered as a part of the total activation energy. [49][50][51][52][53] As a final note, computational results are based on bulk single crystals, and experimentally measured values of diffusional properties are affected by impurity phases, grain boundaries and microstructure, and local variations in composition resulting from synthesis and processing conditions. All the caveats described above should be considered when drawing a quantitative comparison between computational and experimental results.…”
Section: Ab Initio Molecular Dynamics Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…This formation energy of mobile carriers may be significant for pristine, non-doped materials with highly ordered Li sublattices, and should be carefully evaluated and considered as a part of the total activation energy. [49][50][51][52][53] As a final note, computational results are based on bulk single crystals, and experimentally measured values of diffusional properties are affected by impurity phases, grain boundaries and microstructure, and local variations in composition resulting from synthesis and processing conditions. All the caveats described above should be considered when drawing a quantitative comparison between computational and experimental results.…”
Section: Ab Initio Molecular Dynamics Simulationmentioning
confidence: 99%
“…These calculations based on bulk thermodynamics may not fully reflect the actual atomic structure, stoichiometry, chemistry, defects, or microstructures at the interface. While computational studies were performed for the defects in SEs and interfaces, [49][50][51] the atomistic-scale diffusion mechanisms in amorphous SEs, grain boundaries, and SE-electrode interfaces are still largely unclear. To model the ion diffusion in amorphous materials and at the interfaces, large-scale atomistic modeling at the length scale of 1-100 nm is needed.…”
Section: Concluding Remarks and Perspectivementioning
confidence: 99%
“…The Li4SiO4-Li3PO4 solid solution system and the endmember parent phases have been identified as potential solid electrolytes, [15][16][17][18][19][20][21][22][23][24][25][26][27] but not all compositions have been fully characterized. It has been reported that the ionic conductivity can be increased by three orders of magnitude for Li4-xSi1-xPxO4 or -Li3+ySiyP1-yO4 compositions, compared with the two end members, Li4SiO4 and -Li3PO4.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these coatings materials are dense inorganic compounds, such as Al 2 O 3 , TiO 2 and TiN [27] [29]. Among all the coating materials, Li 3 PO 4 is an excellent choice due to its chemical stability, insulating property, ionic conductivity and also mechanical property [30][31] [32].…”
Section: Introductionmentioning
confidence: 99%